PENGARUH KEPEMILIKAN INSTITUSIONAL DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Siska Amelia Al Zahro; Puspita Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of Institutional Ownership and Capital Structure on Firm Value with dividen Policy as a moderating variable in non-cyclical customer companies listed on the Indonesia Stock Exchange in 2019-2024. The sampling method used in this study uses a purposive sampling method, with a quantitative research type. The data used are secondary data, namely the company's annual financial reports. The number of samples used in this study is 25 companies with observations for 6 (six) years, so that 150 observation objects were selected. The analysis technique uses a panel data regression method with the Eviews 12 application tool. The results of the study indicate that institutional ownership does not affect firm value. Capital structure does not affect firm value. Institutional ownership and capital structure affect firm value. Institutional ownership with dividen Policy moderates firm value. Capital structure with dividen Policy does not moderate firm value.